An Analysis of Forest Management Non-Conformities to FSC Standards in Different European Countries - HALALISAN AURELIU-FLORIN; IORAS FLORIN; KORJUS HENN; AVDIBEGOVIC MERSUDIN; MARIC BRUNO; PEZDEVSEK MALOVRH SPELA; ABRUDAN IOAN VASILE (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2015)
The purpose of this study was to assess the most frequent non-conformities identified in different European countries in the processes of forest management certification according to FSC standards. A total of 31 active certificates from five countries (Bosnia and Herzegovina, Estonia, Romania, Slovenia and the United Kingdom) were analysed, including all active certificates (as of 1st of June 2014) from three countries along with a sample of 13 FSC certificates issued in the UK and one certificate covering 95% of the certified forest area in Slovenia. 253 non-conformities in relation to FSC standard requirements were identified as formulated by the audit teams and the most frequently identified non-conformities in the certification process were those related to Principle 6 - Environmental impact (34%), Principle 4 - Community relations and worker’s rights (17%) and Principle 8 - Monitoring and Assessment (13%). A slight positive correlation was noticed between the FSC certified area and the total number of non-conformities, with a closer link in the case of Principle 9 - Maintenance of high conservation value forests, and Principle 4. The non-conformities related to Principles 4, 6 and 9 appeared to be significantly influenced in occurrence by country development; less often in the UK compared with the other four countries.
Keywords: certification; non-conformities; FSC; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Forestry; standards; forest management